Structural properties of ultra-small thorium and uranium dioxide nanoparticles embedded in a covalent organic framework. Issue 18 (28th April 2020) - Moreau, Liane M.; Herve, Alexandre; Straub, Mark D.; Russo, Dominic R.; Abergel, Rebecca J.; Alayoglu, Selim; Arnold, John; Braun, Augustin; Deblonde, Gauthier J. P.; Liu, Yangdongling; Lohrey, Trevor D.; Olive, Daniel T.; et al.
Abstract : ThO2 and UO2 nanoparticles synthesized using a COF-5 template exhibit unpassivated surfaces and provide insight into nanoscale properties of actinides. Abstract : We report the structural properties of ultra-small ThO2 and UO2 nanoparticles (NPs), which were synthesized without strong binding surface ligands by employing a covalent organic framework (COF-5) as an inert template. The resultant NPs were used to observe how structural properties are affected by decreasing grain size within bulk actinide oxides, which has implications for understanding the behavior of nuclear fuel materials. Through a comprehensive characterization strategy, we gain insight regarding how structure at the NP surface differs from the interior. Characterization using electron microscopy and small-angle X-ray scattering indicates that growth of the ThO2 and UO2 NPs was confined by the pores of the COF template, resulting in sub-3 nm particles. X-ray absorption fine structure spectroscopy results indicate that the NPs are best described as ThO2 and UO2 materials with unpassivated surfaces. The surface layers of these particles compensate for high surface energy by exhibiting a broader distribution of Th–O and U–O bond distances despite retaining average bond lengths that are characteristic of bulk ThO2 and UO2 . The combined synthesis and physical characterization efforts provide a detailed picture of actinide oxide structure at the nanoscale, which remains highly underexplored compared to transition metal counterparts.